Experimental Evaluation of Agricultural Drains - Duarte-Olave, V (American Society of Civil Engineers, 2017)
Current models used to design agricultural drains assume that perforated pipes (field drains) are ideal drains, and some models do not include the water entrance resistance factor at pipe perforations. Drainage models used to design agricultural drains assume that perforated pipes (field drains) are ideal drains with no water entrance loss taking place at the drain perforations. However, this may not be a valid assumption for many drainage situations in which radial water flow into the drain is significant in relation to vertical and horizontal water flow. The convergence of streamlines toward the drilling of a real drain causes an additional input resistance (called entrance resistance) to flow and a pressure drop, as compared with an imaginary perfect flow drain. This work evaluates a PVC drains structural mechanical conditions, as related to the drainage extraction area and the water entrance resistance factor, to maximize its water discharge performance. The effects of pipe perforation density, pipe diameter, substrate hydraulic characteristics, and the incorporation of an enveloping screen were studied in an experimental setup to define water extraction efficiency, water entrance resistance factor (αe), and pipe effective radius (ref). This work proves that the water entrance resistance should be taken into account in drainage design because the optimal distance between parallel drains is significantly smaller if pipes are enclosed in a protective screen, compared with pipes without screen, for any drainage extraction area in different substrates. The effects of perforation density and envelope screens are determined by water extraction efficiency for small hydraulic head conditions. © 2016 American Society of Civil Engineers.